Analysis of Waiting Time for Outpatient Services at dr Rasidin Padang Regional Hospital - Sari, Fitri Yunita; Rasyid, Rosfita; Firdawati, Firdawati (Journal La Medihealtico, 2025)
Outpatient waiting periods extended beyond regulatory standards create major problems for hospital service quality because they damage patient satisfaction while also decreasing system performance and affecting institutional public perception. The regulatory standards regarding outpatient waiting times of ≤ 60 minutes were not reflected in the initial survey results at RSUD dr. Rasidin Padang since durations exceeded these limits. Research conducted a mixed-methods sequential explanatory design to explore the elements that lengthen outpatient delays at RSUD dr. Rasidin Padang. A total of 107 outpatients participated using proportional accidental sampling to provide quantitative data while qualitative information came from 14 key informants through semi-structured interviews and 8 participants in a Focus Group Discussion. Research data showed that 76.6% of patients waited for above 60 minutes and the entire process took on average 130 minutes. Insufficient human resources dedicated to medical records and registration combined with specialist doctor indiscipline in exam scheduling together with inadequate facilities that included broken fingerprint devices and insufficient operational computers caused this delay in patient examination start times. The qualitative findings show that Standard Operating Procedures (SOPs) remained in place yet inconsistent execution due to fragmented leadership functions degraded efficiency in services. Insured BPJS patients had to bear excessive administrative procedures that generated extended waiting times than what general patients received.